Breeding in a den of thieves: pros and cons of nesting close to egg predators. Issue 6 (24th June 2016) - de Fouw, Jimmy; Bom, Roeland A.; Klaassen, Raymond H. G.; Müskens, Gerard J. D. M.; de Vries, Peter P.; Popov, Igor Yu.; Kokorev, Yakov I.; Ebbinge, Barwolt S.; Nolet, Bart A.
Abstract: Breeding success of many Arctic‐breeding bird populations varies with lemming cycles due to prey switching behavior of generalist predators. Several bird species breed on islands to escape from generalist predators like Arctic fox Vulpes lagopus, but little is known about how these species interact. We studied brent geese Branta bernicla bernicla that share islands with gulls ( Larus spec.) in Taimyr, Siberia (Russia). On one hand, gulls are egg predators, which occasionally steal an egg when incubating geese leave the nest for foraging bouts. On the other hand, gulls import marine resources to the islands, enriching the soil with their guano. We considered three hypotheses regarding clutch size of brent geese after partial nest predation. According to the "predator proximity hypothesis", clutch size is expected to be smallest close to gulls, because of enhanced predator exposure. Conversely, clutch size is expected to be largest close to gulls, because of the supposedly better feeding conditions close to gulls, which might reduce nest recess times of geese and hence egg predation risk ("guano hypothesis"). Furthermore, gulls may defend their nesting territory, and thus nearby goose nests might benefit from this protection against other gulls ("nest association hypothesis"). We mapped goose and gull nests toward the end of the goose incubation period. In accordance with the latter two hypotheses, goose clutch size decreased with distance to the nearest gull nest in all but the lemming peak year. In the lemming peak year, clutch size was consistently high, indicating that partial nest predation was nearly absent. By mapping food quantity and quality, we found that nitrogen availability was indeed higher closer to gull nests, reflecting guanofication. Unlike predicted by the nest association hypothesis, a predation pressure experiment revealed that egg predation rate decreased with distance to the focal gull nests. We therefore propose that higher food availability close to gulls enables female geese to reduce nest recess time, limiting egg predation by gulls.